Ameloblastic Fibro-Odontoma of the Maxilla in a Pierre-Robin Sequence Patient. (3rd September 2017) - Kufta, Kenneth; Kang, Steve; Alawi, Faizan; Moran, Anna; Panchal, Neeraj
ABSTRACT: Introduction : Pierre Robin sequence (PRS) is a rare disorder classically observed as a triad of features including micrognathia, glossoptosis, and upper airway obstruction. It is associated with a syndrome in about 60% of cases. While odontogenic tumors are common findings in patients with familial adenomatous polyposis and nevoid basal cell carcinoma syndromes, PRS has not been found to be consistently associated with any tumors of the jaw. Case Report : The current report aims to describe a patient with PRS who presented with an extensive ameloblastic fibro-odontoma (AFO) of the maxilla. Conclusion : Continued observation for odontogenic tumors in PRS is necessary.